Prospects for reform of banking supervision - Устинова, Ірина Петрівна; Полторацька, Юлія Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The active system of the bank supervision structural organizational has been considered in the article. The types of the central bank’s participation in exercising of foreign countries’ bank supervision have been defined. The views of the followers of the exercising of the bank supervision in the central bank have been compared with those ones of their opponents. The suitability of the bank supervision separation from the National Bank of Ukraine has been reasoned. In the world there are several alternative systems of organization of supervision of the financial system that vary the degree and nature of the involvement of central banks in this process, that is, whether involved them in monitoring the system of payments, or are guarantors of liquidity in the markets, or supervise the banks, or provide insurance deposit or have a significant role in providing financial security and whether the anti-crisis program, and most importantly the possibility to implement it. The combination of these and many other similar criteria enables three main models for banking regulation. That they are considered in the article. Publication necessity that supervisors should have an efficient system of rapid exchange of information with each other for assessing overall risk and timely appropriate action in the event of problems with any institution that is part of a financial conglomerate, as well as to identify and address shortcomings regulatory activities. The authors concluded that a comprehensive system of banking supervisory system should consist of diagnosing and monitoring audit companies, management of bank supervision in individual bank formation system management strategies of banking supervision, management changes at the bank and the system as analysis of financial condition. All these systems should interact closely, to achieve excellent results in the banks and bank supervision.